2017
DOI: 10.21836/pem20170308
|View full text |Cite
|
Sign up to set email alerts
|

Clodronate disodium for treatment of clinical signs of navicular disease – a double-blinded placebo-controlled clinical trial

Abstract: Summary: Navicular disease (also referred to as palmar foot syndrome or navicular syndrome, although not completely the same) causes lameness in many horses of all activity groups.The objective of this study was to compare clodronate efficacy at improving lameness grade in horses with clinical signs of navicular disease to that of horses given placebo. A randomized, multi-center, double-blinded clinical field study was conducted on 146 horses with forelimb lameness due to navicular disease. Navicular disease w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Our results suggested that CLO did not produce any measurable effects on bone metabolism in juvenile sheep subjected to exercise. Our findings are similar to previous reports that showed bisphosphonates administered to large animals (i.e., horses) were clinically effective in reducing musculoskeletal pain [ 20 , 47 , 76 , 77 ], without causing changes in SBB, BMD, micro-CT measurements, and/or BT [ 19 , 20 , 46 , 47 , 76 , 77 ] using FDA-approved doses [ 46 , 78 ]. This may be due to the lower dose used in large animals compared to humans.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results suggested that CLO did not produce any measurable effects on bone metabolism in juvenile sheep subjected to exercise. Our findings are similar to previous reports that showed bisphosphonates administered to large animals (i.e., horses) were clinically effective in reducing musculoskeletal pain [ 20 , 47 , 76 , 77 ], without causing changes in SBB, BMD, micro-CT measurements, and/or BT [ 19 , 20 , 46 , 47 , 76 , 77 ] using FDA-approved doses [ 46 , 78 ]. This may be due to the lower dose used in large animals compared to humans.…”
Section: Discussionsupporting
confidence: 91%
“…We used a dose in sheep that resembled the pharmacokinetic values of therapeutic CLO administered in horses [48]. The dose used in horses (1.8 mg/kg) has shown clinical efficacy in reducing musculoskeletal pain in multiple studies [20,46,47,77]. However, humans treated for osteoporosis receive 200 mg i. m. every 2 weeks (approximately 2.7 mg/kg based on a 75 kg person) which results in detectable BMD increases [79].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation